Platforms to business relations in online platform ecosystems - Néstor Duch-Brown (European Commission, Joint Research Centre (JRC), 2017)
This report presents evidence on the relationship between online platforms and businesses using these platforms to reach consumers or conduct their operations. First, we review the literature on vertical relationships both from a classic approach and from a multi-sided market perspective. Second, we use survey data to explain the factors behind firms' choice of online channel. Third, we explore the results of a survey passed to firms using platforms to understand their concerns about the behaviour of some of these online gatekeepers. Finally, we offer some conclusions.
Keywords: D23; K11; K12; L86; 330; digital single market; data economy; online platforms; multi-sided markets